Makna Simbolik Dalam Tari Kuda Kepang di Desa Alue Leuhob Kecamatan Cot Girek Kabupaten Aceh Utara - Yeni Zuryaningsih; Cut Zuriana; Naura Atkiya (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the symbolic meanings embedded in the movement variations of the Kuda Kepang dance as practiced in Alue Leuhob Village, Cot Girek Subdistrict, North Aceh Regency. This traditional art form, originally a cultural heritage of Javanese traditions, is preserved by a transmigrant community within the Acehnese society, particularly through the Ronggolawe studio. Utilizing a qualitative descriptive approach, the research reveals that each movement variation in this dance does not merely represent elements of dance aesthetics but also incorporates other branches of art, such as visual arts through the use of props and facial makeup, music through rhythmic accompaniment, and dramatic arts in the trance performance segment. Furthermore, Kuda Kepang dance embodies spiritual symbolism closely tied to spirit summoning, energy unification, and spiritual protection. Typically, the dancers perform in even numbers, ranging from six to eight or more male performers. The floor patterns include vertical, horizontal, and circular formations performed in pairs. This study analyzes thirteen primary movement variations: Sembahan, Milang-Miling, Perangan, Srisig, Entrag, Gedheg, Pacak Gulu, Kuda Lari, Nyawang, Lambaian, Kuda Berjalan, Tanjak, and Tundhuk. Each of these movements serves not only as an aesthetic expression but also as a medium for spiritual communication between the dancers and supernatural forces. These findings suggest that the Kuda Kepang dance functions as a cultural bridge intertwining art, tradition, and spirituality in the community of Alue Leuhob Village, Cot Girek Subdistrict, North Aceh